PWE-270 Are urgent suspected colorectal cancer referrals appropriate? an analysis of 772 two week wait referrals. (22nd June 2015) - Lord, A; Thomas, P; Winter, J; Beck, N
Abstract : Introduction: Following the introduction of a fast track cancer pathway for patients with suspected colorectal cancer (i.e. two week wait clinics) there has been a high demand for this service. Anecdotal experience is that many patients are inappropriately directed to this clinic without meeting NICE criteria. This study aimed to assess appropriateness of GP referrals to a nurse led two week wait colorectal clinic. Method: A database of all consecutive patients referred to our fast track nurse led clinic was prospectively maintained. Records of all patients referred between September 2012 and January 2014 were obtained and examined retrospectively. Referral forms and letters were inspected to assess whether appropriate information was included and whether the referral criteria were met and diagnoses and outcomes were reviewed. Results: A total of 772 patients were included in the study. 46.4% of patients were male. The average age was 67, with a range of 22–91. 66.6% of referrals were deemed to be appropriate. Inappropriate referrals were broken down into clinically inappropriate (22.5% of all referrals) or incomplete referrals (10.9%). Incomplete referrals usually involved completely blank referral forms being sent or a failure to provide any clinical details. The most common reasons referrals were judged to be clinically inappropriate were because symptom duration was under 6 weeks (8.4% of all referrals), the patient was under the age specified by NICE guidelines (7.5%) or the change in bowel habit was constipation rather than looser or more frequent stools (3.2%). During the study period, 57 cancers were identified (7.4% of referrals). 46 of these were colorectal cancers and 11 were tumours at other sites detected on cross sectional imaging. 168 patients had polyps, 73 had inflammatory bowel disease, 112 had other benign pathology (e.g. haemorrhoids, diverticulosis) and 307 had normal investigations. There was a 3.9% cancer detection rate in inappropriate referrals compared to 9.1% in appropriate referrals. All of the non-colorectal cancers were detected in the 'appropriate' group. Conclusion: Whilst the majority of referrals to the fast track clinic were appropriate, almost a quarter did not meet NICE criteria and a significant number were sent without appropriate clinical information. This is consistent with other published data. This study demonstrates a higher cancer detection rate in patients that do meet NICE criteria. This has significant consequences for service provision and resources. Given the clarity of NICE criteria on referral forms, it may be that a perception of long waits for 'routine' clinics or pressure from patients to be seen quickly plays a role. Engagement with GPs to discuss their experience of clinic access and referral pathways may improve compliance. Disclosure of interest: None Declared.